2018
DOI: 10.1016/j.heliyon.2018.e00646
|View full text |Cite
|
Sign up to set email alerts
|

Production and partial characterization of dehairing alkaline protease from Bacillus subtilis AKAL7 and Exiguobacterium indicum AKAL11 by using organic municipal solid wastes

Abstract: Alkaline proteases have applications in numerous industries. In this study, we have isolated and screened proteolytic bacteria from poultry wastes mixed soil and identified two bacterial isolates as Bacillus subtilis AKAL7 and Exiguobacterium indicum AKAL11 based on 16S rDNA sequencing. Maximum level of protease production was achieved after 24 h of fermentation in a basal medium. The optimal temperature, initial pH of the media and agitation for alkaline protease production by these two isolates were 30 °C, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 56 publications
11
38
0
Order By: Relevance
“…Cu 2+ ions may be important for catalysis. It is reported that the activity of alkaline protease from Bacillus sp., Bacillus subtilis, and Bacillus megaterium RRM2 was decreased by Fe 3+ , Hg 2+ , Zn 2+ and Co 2+ (Venugopal and Saramma, 2007;Olajuyigbe and Falade, 2014;Hakim et al, 2018).…”
Section: Impact Of Different Metals Metalloid and Denaturants On Promentioning
confidence: 94%
See 3 more Smart Citations
“…Cu 2+ ions may be important for catalysis. It is reported that the activity of alkaline protease from Bacillus sp., Bacillus subtilis, and Bacillus megaterium RRM2 was decreased by Fe 3+ , Hg 2+ , Zn 2+ and Co 2+ (Venugopal and Saramma, 2007;Olajuyigbe and Falade, 2014;Hakim et al, 2018).…”
Section: Impact Of Different Metals Metalloid and Denaturants On Promentioning
confidence: 94%
“…DB14 protease exhibited interestingly stability in the temperature range of 20 °C and 50 °C. Similarly, Lakshmi et al (2018) reported thermostability of protease from Bacillus cereus strain S8 exhibiting in the temperature range of 30-80 °C, while Hakim et al (2018) showed that Bacillus subtilis AKAL7 protease was stable from 30 °C to 50 °C. Jaouadi et al (2008) determined that the protease of Bacillus pumilus CBS was stable in the temperature range 30-55 °C.…”
Section: Determination Of Thermostability and Ph Stabilitymentioning
confidence: 96%
See 2 more Smart Citations
“…Papaya proteases had pharmaceutical applications such as antitumorals, anti-inflammatory, wound healing and digestive disorder [ 13 ]. The partially purified protease from B. subtilis substantially dehaired cow skin [ 14 ].…”
Section: Introductionmentioning
confidence: 99%